SENAM ASMA MENGURANGI KEKAMBUHAN DAN MENINGKATKAN SATURASI OKSIGEN PADA PENDERITA ASMA DI POLIKLINIK PARU RUMAH SAKIT UMUM DAERAH WANGAYA DENPASAR - I Gede Widjanegara; Ketut Tirtayasa; Alex Pangkahila (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2015)
Asthma gymnastics is one type of exercise therapy that conducted in groups (exercise group) that involving activities of body movement or an essential activity to help the process of respiratory rehabilitation in patients with asthma and it is one of the supporting element in the treatment of asthma. Asthma is a lung disease with characteristics: a reversible airway (but incomplete in some patients) spontaneously or treatment; Inflammation of the airways; Increased airway response to various stimuli (hyperreactivity). This study aims to find out whether asthma gymnastic can reduce the frequency of recurrence of asthma, increase oxygen saturation and physical fitness in patients with asthma in Lung polyclinic of Wangaya hospital Denpasar. This study is an experimental study with the pre and post test control group design. Number of samples were 30 people with asthma consist of 15 patients with asthma as treatment group and 15 patients with asthma as control group. The results showed that in the treatment group have improvement on well controlled relapse and decrease of well uncontrolled relapse. Based on the value Mann Whitney test p = 0.008, it means asthma gymnastics can reduce recurrence in patients with bronchial asthma. Effect of asthma gymnastic on oxygen saturation in treatment group by mean values of % SpO2 increased from 95.1 to 96.5. By using the Mann Whitney p = 0.001, it means asthma gymnastics can improve oxygen saturation in patients with bronchial asthma. Conclusion that administration of asthma gymnastics training for three times a week for eight weeks can reduce the frequency of recurrence, improve oxygen saturation and physical fitness in patients with asthma. Asthma gymnastics will be expected to conduct by asthma sufferer regularly in an effort to control the frequency of asthma attacks effectively.